Chitosan nanoparticles loaded with Lactobacillus rhamnosus bioactive metabolites: Preparation, characterization, and antifungal activity - Aya Abdel-Nasser; Hayam M. Fathy; Ahmed N. Badr; Olfat S. Barakat; Amal S. Hathout (Heliyon)
Aspergillus flavus is a severe danger to worldwide maize (Zea mays) cultivation, due to its extreme toxicity of aflatoxins produced by the fungi, and its ability to cause economic losses while also posing a health concern to humans and animals. Among the measures that may be considered for A. flavus control, applying coatings based on natural ingredients appears to be the most promising. The current work examines the antagonistic ability of Lactobacillus rhamnosus bioactive metabolites added to chitosan nanoparticles against A. flavus on maize kernels. The chitosan nanoparticles loaded with L. rhamnosus bioactive metabolites were characterized using the transmission electron microscope (TEM), zeta potential, size distribution, polydiversity index (PDI), pH, encapsulation efficiency and Fourier transform infrared spectroscopy (FTIR). The TEM revealed that the chitosan nanoparticles loaded with bioactive metabolites were spherical and smooth on the surface, and by increasing the concentration of bioactive metabolites added to the chitosan nanoparticles, the diameter of the chitosan nanoparticle grew. The zeta potential and size distribution values increased as the quantity of L. rhamnosus bioactive metabolites increased in the chitosan nanoparticles. The FTIR analysis indicated the presence of several functional groups, including alkynes, alkene, aliphatic primary amines, and other functional groups. The chitosan nanoparticles loaded with L. rhamnosus bioactive metabolites at a concentration of 7 mg/mL showed significant antifungal activity against A. flavus, reducing their growth in maize kernels by 89.42 % after 10 days of storage. They also reduced the percentage of germination inhibition rate and viability percentage. It could be concluded that adding L. rhamnosus bioactive metabolites to chitosan nanoparticles might have significant implications for food safety by using it in the industry to reduce the fungal contamination of grains.